ULTRASTRUCTURE OF THE MYOCARDIUM OF RATS WITH BLOOD HYPERTENSION IN POSTNATAL ONTOGENESIS - Stechenko, L.; Chuhray, S.; Kuzmenko, J.; Nitrous, L.; Tchaikovsky, Yu. (World of Medicine and Biology, 2015)
The article presents the ultrastructural organization of the myocardium in rats with spontaneous arterial hypertension in postnatal ontogenesis (via 1,7,45,100 and 240 days). It is established that in the early postnatal period of ontogenesis (1доба) for the structural components of cardiomyocytes characteristic phenomena determinacy differentiation. Changes that are detected in the myocardium are of a reactive nature,which obviously relate to the birth, and the myocardium have not yet reached defintive state.In 7добових rats observed active growth of blood vessels, although they do not reach full maturity, which is typical for adult animals. The severity of the destructive traits that were characteristic of newborn rats, much less, that suggests that in recent they are not associated with hypertension. Young (45 and diurnal) animals with hypertension, the infarction is formed completely. However, there are signs as compensatory-adaptive (thinning of the periphery of the endothelial cells) and destructive-degenerative (edema, local lysis of cardiomyocytes and endothelial cells) processes.In stateonly (100 daily) for rats of myocardium and capillaries are characterized by the strengthening of destructive-dystrophic processes in comparison with the previous age group.For rats older age (240 days) is characterized by failure of the compensatory processes in the myocardium and in the capillaries. This is manifested by the subsequent rarefaction of capillaries, the development of hypoxic condition and interstice mucinous edema, decreased activity of biosynthetic and transport processes in all the structures of the myocardium.
Keywords: ultrastructure of the myocardium; arterial hypertension; postnatal ontogenesis